Farmers' Field Day in Vaishali, Bihar in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
This photoset contains pictures taken in relation to climate smart villlage-activities in South Asia in Bihar, India. Photo : Gopal D. Bhatta (CCAFS-SA).